﻿A phylogenetic and morphological study of the Tectaria fuscipes group (Tectariaceae), with description of a new species - Shi-Yong Dong (PhytoKeys, 2022)
The fern species Tectaria fuscipes and morphologically similar species, which are common in tropical and subtropical mainland Asia, constitute a taxonomically confusing group. To better understand species boundaries and relationships within the T. fuscipes group, we conducted phylogenetic analyses of five plastid regions and morphological observations of herbarium specimens and living plants. As a result, we produced a generally well-resolved phylogeny of the T. fuscipes group and related species in Asia. The phylogenetic analyses supported the monophyly of the T. fuscipes group, which includes T. dissecta, T. fuscipes, T. ingens, T. paradoxa, T. setulosa, T. subfuscipes, T. subsageniacea and a new species, but excludes T. kusukusensis. However, T. fuscipes, T. subfuscipes and T. subsageniacea are almost indistinguishable in morphology, which form a complex characterised by the black linear-lanceolate stipe scales. The new species found in southern China and Vietnam is described here as T. fungii. It is similar to the T. fuscipes complex and T. kusukusensis, but differs from the former mainly by its brown-castaneous lanceolate stipe scales and from the latter by having nearly hairless laminae (versus frond axes abaxially bearing copious hairs).